О понятии «перевод» в трудах Юрия Лотмана [The notion of “translation” in the works of Juri Lotman] - Salupere, Silvi (Sign Systems Studies, 2008)
The notion of “translation” in the works of Juri Lotman. The present article deals with the concept of “translation“ and other related concepts (“re-codification”, “exact translation”, “adequate translation”, “equivalence”, “transformation”) in the works of Juri Lotman, demonstrating among other things possible relations with the ideas of Roman Jakobson and Louis Hjelmslev. Two main areas of research have been distinguished where the concept of “translation” clearly stands out. First are Juri Lotman’s works on structural poetics, where he discusses mainly the specifics of translating artistic texts. The other is his articles on the typology of cultures where translation is seen as a dialogue, the principal operational mechanism of culture.